2015
DOI: 10.18433/j3h89s
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Skin Penetration of Hydrophilic and Lipophilic Compounds by pH-sensitive Liposomes

Abstract: -PURPOSE: Enhance skin penetration of hydrophilic and lipophilic compounds using liposomes that are responsible to the pH of the skin surface. METHODS: pH-sensitive liposomes were prepared by a thin layer and freeze-thaw method with dioleoyl phosphatidyl ethanolamine and cholesteryl hemisuccinate. Liposomal fusion with stratum corneum lipid liposomes was measured using fluorescence resonance energy transfer. Particle diameter and zeta potential of the liposomes after fusion were measured by dynamic light scatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Hydrophilic drugs like PF often suffer from a low encapsulation rate and easily leak out during the preparation of liposomes due to their poor affinity with the phospholipid membrane. 34 We found that the EE of PF could be significantly improved when using the reverse-phase evaporation method, which was superior to the injection method and the film dispersion method. This effect might be due to the improvement in the concentration of hydrophilic drugs in the inner water phase by the reversephase evaporation method, leading to the formation of large unilamellar vesicles.…”
Section: Discussionmentioning
confidence: 81%
“…Hydrophilic drugs like PF often suffer from a low encapsulation rate and easily leak out during the preparation of liposomes due to their poor affinity with the phospholipid membrane. 34 We found that the EE of PF could be significantly improved when using the reverse-phase evaporation method, which was superior to the injection method and the film dispersion method. This effect might be due to the improvement in the concentration of hydrophilic drugs in the inner water phase by the reversephase evaporation method, leading to the formation of large unilamellar vesicles.…”
Section: Discussionmentioning
confidence: 81%
“…Despite various approaches in developing cosmetics, these products have limited skin penetration due to the skin barrier. Therefore, various molecular, chemical, and morphological studies have been performed on increasing the skin penetration of various topical agents18192021.…”
Section: Discussionmentioning
confidence: 99%
“…Despite various approaches in developing cosmetics, these products have limited skin penetration due to the skin barrier. Therefore, various molecular, chemical, and morphological studies have been performed on increasing the skin penetration of various topical agents [18][19][20][21] .…”
Section: Discussionmentioning
confidence: 99%